The Effect of Employee Technical Skills and Employee Soft Skill Abilities on Training Programs and Mediated on Employee Performance - putri, RDN DWI PUTRIANI; Mulyati, Sri; Jonathan, Tiardo; Sestri Goestjahjanti, Francisca; Winanti, Winanti; Mendrofa, Yeremia; Farhan, Akhmad; Purno, Marhaendro; Mirda Santi, Neta; Kulla Himmy’azz, Istajib; Tiara, Beby (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
There are still many technical skills, soft skills abilities and training programs that are low and below average standards can affect employee performance. This study aims to determine the effect of technical skills, soft skills abilities and training programs as intervening variables on employee performance. The population in this study were 787 employees with age criteria 18 - 50 years. The sample used was 89 people. The type of research used is associative. The research method of quantitative analysis consisting of the training program variable is able to mediate employee technical skills on employee performance with a value of 2,400 with a significance level of 0.019 <0.05, so it has a significant effect. Variable The training program is able to mediate the ability of employee soft skills on productivity with a value The magnitude of the indirect effect of employee technical skills (X1) on the training program (Y) is 0. 315 with a significance value of 0.008 <0.05 and the training program (Y) on employee performance (Z) is 0.313 with a significance value of 0.004 <0.05. then the magnitude of the indirect effect is 0.315 x 0.313 = 0.0985. the magnitude of the total effect is equal to = 2.935 + (0.315 x 0.313) = 3.0335. The training program variable is able to mediate the ability of employee soft skills on employee performance with a value of 2.415 with a significance level of 0.018 <0.05, it can be concluded that it has an effect. The magnitude of the indirect effect of employee soft skills (X2) on the training program (Y) is 0.566 with a significance value of 0.000 <0.05 and the training program (Y) on employee performance (Z) is 0.313 with a significance value of 0.004 <0.05. then the magnitude of the indirect effect is 0.566 x 0.313 = 0.07358. the magnitude of the total effect is equal to = 2.935 + (0.566 x 0.313) = 3.00858.